Problem-Based Learning: Improving Students' Creative Thinking Skills on Mangrove Ecosystem Preservation - Papilaya, Pamella Mercy; Tuapattinaya, Prelly. M.J. (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
Damage to the coastal environment due to low public awareness in maintaining mangrove biodiversity is an urgent problem to overcome. One of the impacts that arise is the degradation of mangrove ecosystems that threaten environmental balance. This study aims to analyze and evaluate students' creative thinking skills in designing solutions to mangrove management problems through the application of Problem-Based Learning. This research is a combination of qualitative and quantitative methods with a mixed methods design. The research subjects involved 86 junior high school students, consisting of 23, 20, 21, and 22 students from four different schools. Data collection techniques were conducted through observation, interviews, and questionnaires. The instruments used included observation sheets, interview guidelines, perception questionnaires, and creative thinking ability tests. Data analysis was done descriptively qualitative and quantitative. The results showed that the problem-based learning approach significantly encouraged the development of students' creative thinking skills, especially in the aspects of fluency, flexibility, originality, and elaboration in developing mangrove arrangement solutions. The conclusion of this research is that the application of problem-based learning model is proven effective in improving students' creativity in solving environmental problems. This research implies that the integration of project-based contextual learning can be a relevant learning strategy in forming a generation that cares about the environment and has high-level thinking skills.